2010
DOI: 10.1007/s00122-009-1250-8
|View full text |Cite
|
Sign up to set email alerts
|

An extensive study of the genetic diversity within seven French wine grape variety collections

Abstract: The process of vegetative propagation used to multiply grapevine varieties produces, in most cases, clones genetically identical to the parental plant. Nevertheless, spontaneous somatic mutations can occur in the regenerative cells that give rise to the clones, leading to consider varieties as populations of clones that conform to a panel of phenotypic traits. Using two sets of nuclear microsatellite markers, the present work aimed at evaluating and comparing the intravarietal genetic diversity within seven wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 44 publications
3
54
1
2
Order By: Relevance
“…The SSR analysis in current study has enabled to differentiate rootstock varieties (SO4, Ramsey and Dog Ridge) from other studied varieties. This supports the efficacy of SSR technique to differentiate and study the genetic relationship in Tunisian, Spanish, and French grapes (Zoghlami et al, 2009;Moreno-Sanz et al, 2011;Pelsy et al, 2010). The power of SSR technique was most effective to characterize all tested grape varieties through the production of unique positive and/or negative markers (Table 2).…”
Section: The Polymorphism Analysis Of Ssr Markerssupporting
confidence: 67%
“…The SSR analysis in current study has enabled to differentiate rootstock varieties (SO4, Ramsey and Dog Ridge) from other studied varieties. This supports the efficacy of SSR technique to differentiate and study the genetic relationship in Tunisian, Spanish, and French grapes (Zoghlami et al, 2009;Moreno-Sanz et al, 2011;Pelsy et al, 2010). The power of SSR technique was most effective to characterize all tested grape varieties through the production of unique positive and/or negative markers (Table 2).…”
Section: The Polymorphism Analysis Of Ssr Markerssupporting
confidence: 67%
“…Pelsy et al (2010) reported that, traditionally, clones are attributed to a variety on the basis of several common ampelographic traits, although phenotypic variations between clones of the same variety are often observed and accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Among them only few hundred are cultivated for commercial wine production (Truel et al, 1980). The management of these collections requires attention to avoid redundancy, to track introductions that were wrongly assigned to a cultivar and to assist clone selection (Pelsy et al, 2010). So, identification of the plant material is crucial and represents the first step in germplasm management (Cipriani et al, 2010;Laucou et al, 2011).…”
Section: Dna Isolation Rapd and Issr Amplificationmentioning
confidence: 99%